2021
DOI: 10.1109/tie.2020.3021638
|View full text |Cite
|
Sign up to set email alerts
|

Latency Analysis of Multiple Classes of AVB Traffic in TSN With Standard Credit Behavior Using Network Calculus

Abstract: Time-Sensitive Networking (TSN) is a set of amendments that extend Ethernet to support distributed safety-critical and real-time applications in the industrial automation, aerospace and automotive areas. TSN integrates multiple traffic types and supports interactions in several combinations. In this paper we consider the configuration supporting Scheduled Traffic (ST) traffic scheduled based on Gate-Control-Lists (GCLs), Audio-Video-Bridging (AVB) traffic according to IEEE 802.1BA that has bounded latencies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…The relation between the IEEE 802.1Qbu and IEEE 802.3br amendments is represented in Figure 8, where it is possible to notice that two different MAC layers are introduced, eMAC and pMAC, to handle, respectively, express and preemptable traffic. The effect of the preemption capability was evaluated in several works [106][107][108][109][110]. Conversely, authors of [111] underlined the importance to study the impact of the preemption activity also on the delay introduced in the Best Effort (BE) traffic communication.…”
Section: Frame Preemption and Interspersing Express Traffic (Iet)mentioning
confidence: 99%
“…The relation between the IEEE 802.1Qbu and IEEE 802.3br amendments is represented in Figure 8, where it is possible to notice that two different MAC layers are introduced, eMAC and pMAC, to handle, respectively, express and preemptable traffic. The effect of the preemption capability was evaluated in several works [106][107][108][109][110]. Conversely, authors of [111] underlined the importance to study the impact of the preemption activity also on the delay introduced in the Best Effort (BE) traffic communication.…”
Section: Frame Preemption and Interspersing Express Traffic (Iet)mentioning
confidence: 99%
“…Zhang et al [29] reduced the effect of higher priority flows on the lower priority traffic by selecting an appropriate transmission cycle and proper scheduling unit. On the other hand, the researchers in [4], [30]- [32] presented formal AVB latency analysis based on predefined TT schedules. The authors demonstrated some improvements in the CBS limitations.…”
Section: Related Workmentioning
confidence: 99%
“…Designing appropriate GCLs in all selected nodes while guaranteeing the quality-of-service (QoS) requirements for critical time flows is a complex and vital problem. The designer has to pay the highest attention to two significant aspects; the TT latency requirements, and the impact on unscheduled real-time traffic [4]. Although several safe analytical models have been proposed to speed TT scheduling, they still have a degree of pessimism in latency evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…Since the standard 802.1Q [1] now supports multiple number of AVB classes, we extend the previous analysis work of supporting two classes [28] and three classes [29] to arbitrary number of AVB classes. The extension proof of credit bounds for arbitrary number of AVB classes can be found in our previous work [34]. Although [34] is the NC-based performance analysis for combined TAS and CBS, and TT transmission delays AVB traffic, AVB credits will not be affected by TT traffic if credit frozen during TT window and the protection interval ("guard band" (GB)), which is one of the cases discussed in [34].…”
Section: Credit Based Shaper (Cbs)mentioning
confidence: 99%
“…Zhao et al [33] propose the performance analysis of AVB traffic under the coexistence of CBS and TAS. The same authors [34] extend the timing analysis for arbitrary number of AVB classes under the same architecture of TAS+CBS, considering both standard credit behavior and more generally assumed credit behavior but deviating from the standard 802.1Q [1]. Mohammadpour et al [35] consider the combination of non-time-triggered control-data traffic (CDT), CBS and ATS, and give the latency and backlog bounds for the traffic of CBS affected by ATS.…”
Section: Introductionmentioning
confidence: 99%